Sistem Pendukung Keputusan Penilaian Kinerja Program Studi Diploma III - Dwi Agus Diartono (Dinamik, 2003)
A university as an educative institution needs an assessment for the programs it has. In order to conduct such assessment , some components need to be assessed based on the internal and external factors. It is necessary to establish a decision support system toward the performance of the department. It can help the decision maker to know the condition occurred in this department. 'l he assessment of the study program's performance for evaluating can be done by underlining the components that will be assessed by making the model. The model which is prepared by applying some rules, stated in accreditation board, will be used as a reference in performance assessment for  Diploma III program. By applying a model toward the assessment criteria from the related department, it will help us to get the result. The achieved result is in form of the total score from the assessment, the score is devided into 5 class excellent, very good, good, sufficient and poor. Consequently, the report of resulting assessment can be to determine some steps to improve or maintain the recent achievement. By applying the decision support system of the department’s performance , it allow a decision maker to be able to monitor the department or the study program.